Novel therapies for myelofibrosis. Issue 10 (3rd October 2015) - Stein, Brady L.; Cervantes, Francisco; Giles, Francis; Harrison, Claire N.; Verstovsek, Srdan
Abstract : Myelofibrosis (MF), including primary, post-essential thrombocythemia and post-polycythemia vera MF, associates with a reduced quality of life and shortened life expectancy. Dysregulation of the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway is prominent, even in the absence of the JAK2 V617F mutation. Therefore, all symptomatic MF patients may potentially derive benefit from JAK inhibitors. Despite the efficacy of JAK inhibitors in controlling signs and symptoms of MF, they do not eradicate the disease. Therefore, JAK inhibitors are currently being tested in combination with other novel therapies, a strategy which may be more effective in reducing disease burden, either by overcoming JAK inhibitor resistance or targeting additional mechanisms of pathogenesis. Additional targets include modulators of epigenetic regulation, pathways that work downstream from JAK/STAT (i.e. mammalian target of rapamycin/AKT/phosphoinositide 3-kinase) heat shock protein 90, hedgehog signaling, pro-fibrotic factors, abnormal megakaryocytes and telomerase. In this review, we discuss novel MF therapeutic strategies.